Nanny families : practices of care by nannies, au pairs, parents and children in sweden. - ELDN, SARA (Sociology of children and families, 2019)
Paying privately for childcare is a growing phenomenon worldwide, a trend mirrored in Sweden despite the prevalence there of publicly funded daycare. This book combines theories of family practices, care and childhood studies with the personal perspectives of nannies, au pairs, parents and children to provide new understandings of what constitutes care in nanny families.